Madrasah Aliyah-Based Culture Development 5S (Seiri, Seiton, Seiso, Seiketsu and Shitsuke) - Bahronil Ulum; Tomasi Elaine; Lei Richard (P3M IAI Nusantara Batang Hari, 2022)
The problems that arise in the culture of Madrasah Aliyah are the absence of a conducive madrasa culture, improvements to madrasas tend to be only in physical form, a lack of understanding of the importance of madrasa culture, and the absence of optimal efforts in the framework of moral development through madrasa culture. This study aims to describe and identify positive changes after the implementation of values ​​and morals education through the development of the 5S-based Madrasah Aliyah culture (Seiri, seiton, seiso, seiketsu and Shitsuke) in Bantur District, Malang Regency. This research is an action research at Madrasah Aliyah which is in Bantur District, Malang Regency in the 2021/2022 academic year. The application of 5S (Seiri, seiton, seiso, seiketsu and Shuketsi) at Madrasah Aliyah in Bantur District, Malang Regency is in the form of instilling an organized, neat and clean attitude to students as well as maintaining these conditions and transmitting them to others. After implementing these actions, good habits that are formed in students include being organized, neat, clean, obedient to rules, diligent, and thorough.